Business intelligence and big data : 7th European Summer School, eBISS 2017, Bruxelles, Belgium, July 2-7, 2017, Tutorial lectures /: 7th European Summer School, eBISS 2017, Bruxelles, Belgium, July 2-7, 2017, Tutorial lectures. (2018) - Unknown
No abstract available